GLIM in chronic kidney disease: What do we need to know? - Silva, Maryanne Zilli Canedo [UNESP]; Cederholm, Tommy; Gonzalez, Maria Cristina; Lindholm, Bengt; Avesani, Carla Maria (Elsevier, 2023)
The lack of consensus on diagnostic criteria for malnutrition has hampered developments in research and clinical practice pertaining to nutrition. This opinion paper describes the applicability and other aspects of using the Global Leadership Initiative on Malnutrition (GLIM) criteria for diagnosing malnutrition in patients with chronic kidney disease (CKD). We examine the purpose of GLIM, the particularities of CKD that can affect the nutritional and metabolic status and the diagnosis of malnutrition. In addition, we make an appraisal of previous studies that used GLIM in the context of CKD and discuss the value and relevance of using the GLIM criteria in patients with CKD.
Keywords: Chronic kidney disease; Dialysis; Glim; Global leadership initiative on malnutrition; Malnutrition; Nutritional assessment